2005
DOI: 10.2169/internalmedicine.44.934
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Clinical Courses of the Opticospinal and Conventional Forms of Multiple Sclerosis in Japan

Abstract: We evaluated the clinical courses of 216 patients with multiple sclerosis (MS) diagnosed according to the recommended diagnostic criteria of McDonald et al (10). Sixty-five patients clinically displaying selective involvement of the optic nerves and spinal cord were classified as opticospinal MS (OS-MS), while the other 151 showing disseminated involvement of the central nervous system were classified as conventional MS (C-MS). The disease duration did not differ significantly between the two subtypes (11.2 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…A first attack interval longer than six months almost always predicts relapsing disease 79 . The relapsing course in this Western series is compatible with the characteristic polyphasic course of the opticospinal MS described in Asian countries 40,131 . Patients with relapsing NMO tend to have a greater number of attacks than relapsing-remitting MS patients in similar follow-up duration 132 .…”
Section: Clinical Featuressupporting
confidence: 84%
See 1 more Smart Citation
“…A first attack interval longer than six months almost always predicts relapsing disease 79 . The relapsing course in this Western series is compatible with the characteristic polyphasic course of the opticospinal MS described in Asian countries 40,131 . Patients with relapsing NMO tend to have a greater number of attacks than relapsing-remitting MS patients in similar follow-up duration 132 .…”
Section: Clinical Featuressupporting
confidence: 84%
“…In Asian countries the term "Devic's disease" is strictly used to identify these cases 131 . Wingerchuk et al 8 have demonstrated that patients with unilateral optic neuritis are indistinguishable from those with bilateral optic neuritis and the interval over which patients develop the index events has no diagnostic significance.…”
Section: The Spectrum Of Devic's Neuromyelitis Opticamentioning
confidence: 99%
“…Patients with lesions at multiple sites in the CNS, including the cerebrum, cerebellum, or brainstem, are classifi ed as having conventional MS. OS-MS patients show a higher age of onset, female preponderance, and a higher score in Kurtzke's expanded disability status scale than conventional MS patients. 17 The proportion of the opticospinal variant of MS in Japan is seven times that in Britain (42% vs. 6%). 18 Lau et al 19 reported that 36% of MS cases in Hong Kong (southern Chinese) were the opticospinal variant.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with relapsing-remitting MS can be classifi ed clinically into two groups: those with opticospinal MS (OS-MS) and those with conventional MS. 17 MS in which the main lesions are confi ned to the optic nerve and spinal cord, with no evidence of lesions in the cerebrum or cerebellum, is classifi ed as OS-MS. Patients with lesions at multiple sites in the CNS, including the cerebrum, cerebellum, or brainstem, are classifi ed as having conventional MS. OS-MS patients show a higher age of onset, female preponderance, and a higher score in Kurtzke's expanded disability status scale than conventional MS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although the disease is common presentation of MS in eastern Asian countries [11][12][13][14][15][16][17] and well studied in Japan [5][6][7][8]18], it is not a well known entity in the Middle East region where it is believed that the clinical presentation and course of MS is similar to that of western countries [19][20][21][22][23]. The aim of this study was to review demographic data, clinical course, MRI findings and CSF changes of OSMS in Iran where it is an uncommon clinical presentation of MS [24].…”
Section: Introductionmentioning
confidence: 99%